Management of cancer treatment-related fatigue in advanced breast cancer patients: an expert committee’s opinion - Bécourt, Stéphanie; Abadie-Lacourtoisie, Sophie; Calvat, Thierry; Coudurier-Curveur, Isabelle; Fiteni, Frédéric; Mery, Benoîte; Meynard, Guillaume; Scotté, Florian; Vaflard, Pauline; Zelek, Laurent (Frontiers in Oncology, 2025)
Cancer-related fatigue (CRF) is a frequent and complex adverse event associated with advanced breast cancer (ABC). CRF intensity and impact on a patient’s daily life are often exacerbated by cancer treatments. This specific manifestation, known as cancer treatment related fatigue (CTRF), begins with treatment onset and can persist beyond its course. CTRF is not unavoidable; its effect can be reduced through careful management and differential diagnosis from CRF. This article aims to review current recommendations for assessing and managing fatigue and present an expert opinion on priority actionable actions for evaluating and alleviating fatigue in ABC patients. In addition, to better understand the current standard of care and management options for ABC patients with fatigue, a quantitative survey was conducted from July to September 2023 through online standardized questionnaire containing identical questions between oncologists (N = 43) and ABC patients (N = 132) in France. Results confirm fatigue’s complexity and multidimensional nature. Insufficient time and lack of communication during consultations contribute to ineffective diagnosis and management of fatigue, highlighting the need for improvement through better communication.